The Impact of Affirmative Action on Labor Demand: A Test of Some Implications of the Le Chatelier Principle - Griffin, Peter (The Review of Economics and Statistics, 1992)
This paper presents an alternative approach to measuring the impact of affirmative action on firms. Affirmative action is modeled as a series of hiring quotas. If the quotas are binding, then a firm subject to affirmative action will operate with greater costs of production, have less elastic demand for inputs, and be less able to substitute between most inputs. The results are consistent with the hypothesis that affirmative-action regulations significantly constrain firms' behavior. Own-wage elasticities are less elastic and most inputs are less substitutable for constrained firms. Further, affirmative action raises costs by 6.5 percent for firms subject to the program. Copyright 1992 by MIT Press.